Effects of Estrogen on Proliferation and Apoptosis of Osteoblasts through Regulating GPER/AKT Pathway: Effects of Estrogen on Osteoblasts - Zhang, Yang; Jiang, Tianlong; Ni, Shenghui; Liu, Wenbo; Luo, Peng; Hao, Shimin; Wang, Penghao; Guo, Lei (Cellular and Molecular Biology, 2022)
This experiment was carried out to study the effects of estrogen on the proliferation and apoptosis of osteoblasts through regulating the G protein-coupled estrogen receptor (GPER)/protein kinase B (AKT) pathway. For this aim, osteoblasts were cultured in vitro and divided into control group, estrogen group and inhibitor group after passage. The osteoblasts in the control group were cultured normally, estrogen intervention was made in the estrogen group and G15 inhibitor intervention was made in the inhibitor group. After intervention for 24 h, osteoblasts were collected for detection. The positive expression of GPER and the double-positive expression of Tom20/Lamp2 were detected via immunofluorescence assay. The protein expressions of GPER, AKT and phosphorylated (p)-AKT were detected via Western blotting. The mRNA expression of GPER was detected via qPCR. Moreover, the autophagosomes were observed under a transmission electron microscope, and the apoptosis and cell proliferation were detected via terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay and cell counting kit-8 (CCK8) assay, respectively. Results of the immunofluorescence assay revealed that the positive expression of GPER in the estrogen group was higher than that in the control group and inhibitor group (p<0.05), while the double-positive expression of Tom20/Lamp2 in the estrogen group was lower than that in control group and inhibitor group (p<0.05). According to the results of Western blotting, the relative protein expression of AKT had no differences among the three groups (p>0.05), while the relative protein expressions of GPER and p-AKT in the estrogen group were higher than those in the control group and inhibitor group (p<0.05). The results of qPCR showed that the relative mRNA expression of GPER in the estrogen group was higher than that in the control group and inhibitor group (p<0.05). There were a small number of autophagosomes in osteoblasts in the control group and inhibitor group, while the number of autophagosomes in osteoblasts was smaller in the estrogen group. Besides, the estrogen group had a remarkably lower apoptosis rate of osteoblasts than the control group and inhibitor group and a remarkably higher proliferation rate than the control group and inhibitor group. Then estrogen can inhibit the mitochondrial autophagy of osteoblasts by regulating the GPER/AKT pathway, thereby inhibiting apoptosis and promoting cell proliferation.